Evaluatıon Of Lower Lıp Profıle In Cleft Lıp And Palate Patıents - M. Okan Akçam; T. Ufuk Toygar; Ayça Arman (Galenos Yayinevi, 2003)
The aim of this study was to evaluate the lower lip morphology and posture of pre-peak cleft lip and palate (CLP) patients comparatively with skeletodental Class I normals and post-peak unilateral CLP subjects. The study material consisted of lateral cephalometric and hand-wrist radiographs obtained from a total of 38 CLP patients, 24 pre-peak unilateral (Mean age: 12.86± 0.85 years), 14 post-peak unilateral (Mean age: 16.53±0.77 years) and 20 control individuals (Mean age:12.33±0.85 years) with Class I occlusion and a harmonious profile. Cephalometric landmarks were double-digitized and the measurements were calculated by a computer program. Besides conventional dentofacial variables, the lower lip area was also measured by using a digital planimeter on the cephalometric tracings. Bonferroni test was performed to evaluate the differences between the pre-peak CLP and the control group while t-test was used to evaluate the defferences between pre and post peak unilateral CLP groups. The lower lip area was 3.46±0.27cm2 in the pre-peak CLP group and no statistically significant difference was found in comparison with the control (4.42±0.24 cm2). The lower lip area was found as 4.38+0.19cm2 in the post-peak unilateral group and was significantly different from the pre-peak group (p<0.001). The results of this study imply that the lower lip thickness of CLP patients increases after puberty. The reason of this increase may be a compensatory mechanism to reduce the increased inter-labial gap due to the short upper lip seen in CLP subjects.